Direct Energy - Mitofsky, Andrea M.; Open Textbook Library (Open Textbook Library, 2018)
Direct Energy Conversion discusses both the physics behind energy conversion processes and a wide variety of energy conversion devices. A direct energy conversion process converts one form of energy to another through a single process. The first half of this book surveys multiple devices that convert to or from electricity including piezoelectric devices, antennas, solar cells, light emitting diodes, lasers, thermoelectric devices, and batteries. In these chapters, physical effects are discussed, terminology used by engineers in the discipline is introduced, and insights into material selection is studied. The second part of this book puts concepts of energy conversion in a more abstract framework. These chapters introduce the idea of calculus of variations and illuminate relationships between energy conversion processes.
1. Introduction -- I. Survey of Energy Conversion Devices -- 2. Capacitors and Piezoelectric Devices -- 3. Pyroelectrics and Electro-Optics -- 4. Antennas -- 5. Hall Effect -- 6. Photovoltaics -- 7. Lamps, LEDs, and Lasers -- 8. Thermoelectrics -- 9. Batteries and Fuel Cells -- 10. Miscellaneous Energy Conversion Devices -- II. Theoretical Ideas -- 11. Calculus of Variations -- 12. Relating Energy Conversion Processes -- 13. Thomas Fermi Analysis -- 14. Lie Analysis
In English.
Description based on online resource
Keywords: Engineering -- Textbooks; Electrical Engineering -- Textbooks